Converging or diverging? A comparative analysis of trends in contingent employment practice in Europe over a decade - Tregaskis, Olga; Brewster, Chris (Journal of International Business Studies, 2006)
This paper makes a unique contribution to the HRM convergence/divergence debate by examining whether organisations operating in Europe, over the 10-year time period preceding 2000, are converging in their adoption of contingent employment practice. The susceptibility of contingent employment practice to both convergent and divergent pressures acts as a useful analytical lens. Data are drawn from organisations operating in Germany, Spain, Sweden, the Netherlands and the UK in 1991 (2918 organisations), 1995 (2048 organisations) and 2000 (1555 organisations). The results suggest that convergence is limited by the institutional embeddedness of organisations.